2017
DOI: 10.1186/s12891-017-1561-x
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 ameliorates TNF-α induced meniscus degeneration in mature meniscal tissue in vitro

Abstract: BackgroundJoint inflammation causes meniscus degeneration and can exacerbate post-traumatic meniscus injuries by extracellular matrix degradation, cellular de-differentiation and cell death. The aim of this study was to examine whether anti-inflammatory interleukin-10 exerts protective effects in an in vitro model of TNF-α-induced meniscus degeneration.MethodsMeniscus tissue was harvested from the knees of adult cows. After 24 h of equilibrium explants were simultaneously treated with bovine TNF-α and IL-10. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…Iwata et al revealed that CD318 is a CD146 negative subset of bone marrow fibroblasts and regulates cytokine expression 44. Previous studies have shown that inflammatory cytokines such as IL-1β and TNF-α induce meniscus metabolic responses and result in degeneration 28 45. In our study, IL-1β was used to induce the inflammatory response in human meniscus cells.…”
Section: Discussionmentioning
confidence: 70%
“…Iwata et al revealed that CD318 is a CD146 negative subset of bone marrow fibroblasts and regulates cytokine expression 44. Previous studies have shown that inflammatory cytokines such as IL-1β and TNF-α induce meniscus metabolic responses and result in degeneration 28 45. In our study, IL-1β was used to induce the inflammatory response in human meniscus cells.…”
Section: Discussionmentioning
confidence: 70%
“…The roles of matrix metalloproteinases 13 (MMP13) and an 'aggrecanase' known as a disintegrin and metalloproteinase with thrombospondin motifs − 5 (ADAMTS5), in OA through the degradation of ECM are well established [12][13][14]. It is also clear that type X collagen (COL10A1) is a marker of fibrochondrocyte hypertrophy in meniscus [9,15], and CEBPβ contributes to the pathophysiological process of OA [16,17]. These genes whose expression level corretated with the extent of cartilage degeneration might be considered as markers of articular deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…Lower circulating IL-10 corresponds with higher joint effusion of TNF-α, localized and systemic indices of cartilage degeneration, and greater histological evidence of joint osteoarthritis following anterior cruciate ligament transection in experimental rabbits 40 . In humans, a lower serum IL-10 is arguably mirrored by a decrease in synovial fluid IL-10 12 , 41 , which in turn, could compromise joint integrity by exacerbating blood-induced cartilage damage 42 , and as demonstrated in vitro, minimize the protection against pro-inflammatory cytokine induced damage 22 25 . Therefore, in the absence of a robust TNF-α alteration, it is plausible that a lower serum IL-10 concentration following an anterior cruciate ligament injury could be detrimental to the joint structure by compromising the anti-inflammatory protection against pro-inflammatory cytokine-mediated cartilage loss and consequentially increase the risk of developing knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The localized presence of TNF-α could increase the risk of osteophyte progression, joint space narrowing 19 , cartilage degradation 20 , and lower IL-10 expression 21 . IL-10 decreases TNF-α production and TNF-α mediated events associated with osteoarthritis development 22 25 , thereby suggesting the pathophysiological importance of a regulated anti- and pro-inflammatory cytokine balance on joint integrity. Although an increased production of IL-10 and TNF-α from whole blood associates with the progression in knee osteoarthritis 26 , and preliminary results indicate that local and circulating cytokine concentrations decrease with severe compared to moderate knee osteoarthritis 27 , 28 , it is unknown if the circulating pro- to anti-inflammatory cytokine balance (i.e., ratio) is altered with the radiographic severity in knee osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%